Modernisierung des Arbeitskampfrechts zu einem Tarifverhandlungsrecht - Volker Rieble (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2005)
– Judicial decisions concerning industrial action have strengthened the right to strike and made lockouts virtually impossible. Employers respond to such a shift in the power on the labour market with relocations and power on the goods market. In addition the trade unions are threatened by self-interested functional elites. All this calls into question the suitability of industrial action for resolving conflicts. If the conflict-resolving function of industrial action is to be retained, restrictions in the right to strike are necessary. In order to avoid detrimental industrial action it is necessary to attempt effective mediation. It is imperative that advance notice be given of industrial action. The employees must also be held responsible for effects of detrimental industrial action on third-party enterprises, as a risk of the industrial action. Every strike requires an authorising strike ballot in the trade union. An effective emergency service order must be established for firms providing services for the public. The works council must not be able to use participation rights and information rights in order to influence the dispute.
Keywords: 330; Arbeitskampf - Recht; Streikrecht - Änderung; Aussperrung; Tarifpolitik; Tarifrecht; Tarifverhandlungen - Recht; Konfliktmanagement; Macht; Schlichtung; Arbeitgeberverband; Gewerkschaft